Pendekatan ekonomi sirkular sebagai strategi pembangunan berkelanjutan di Indonesia - Irawan, Doni; Cahaya Marita, Adelia; Nurcahyaningtyas (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2024)
This study aims to analyze the effect of circular economy implementation on the three dimensions of sustainable development in Indonesia. The data used is panel data, a combination of cross-section data from 34 provinces in Indonesia, and time series data for 2019-2022. The research data is sourced from the Central Statistics Agency (BPS) and the Ministry of Environment and Forestry (KLHK) publications. The analysis method used is panel data regression with the help of EViews 10 software. This research will estimate three models to see the impact of circular economy implementation in supporting the three dimensions of sustainable development. The result shows that implementing a circular economy in the resource efficiency dimension has supported sustainable development in economic, social, and environmental goals. Meanwhile, the implementation of a circular economy in the dimension of resource management and environmental preservation has not been optimized so it has not supported the achievement of sustainable development of economic, environmental, and social goals.